On The Class of (K-N)* Quasi-N-Normal Operators on Hilbert Space - Dawood Muhsin, Salim; Mohammed Khalaf, Ahmed (Iraqi Journal of Science, 2021)
In this paper, we will give another class of normal operator which is (K-N)*quasi-n-normal operator in Hilbert space, and give some properties of this conceptas well as discussion the relation between this class with another class of normaloperators.